Neo-democracy in educational policy-making: a critical case study of neoliberal reform in Massachusetts. Issue 2 (4th March 2017) - Piazza, Peter
Abstract: This paper explores changes to the educational policy-making arena through case study analysis of a Massachusetts law passed in 2012 that limits seniority-based job protections for public K-12 teachers. I use data from interviews with policy stakeholders, observations of public meetings, and policy artifacts to explore struggles over democratic engagement in what unfolded as a highly undemocratic policy development process. Using the policy cycle framework, I explore the ways that political pressure and political discourses shaped the policy development process through various contexts of political struggle. Ultimately, I argue that the case is indicative of what I am calling 'neo-democratic' decision-making, in which high-level interest group conflict leads to narrow forms of democratic engagement.